Informational behavior on the Internet in students of Information Sciences, Universidad de Holguín = Comportamiento informacional en Internet en estudiantes de Ciencias de la Información, Universidad de Holguín - María Virginia González Guitián; María Rosa de Zayas Pérez; María Mercedes Núñez Grillo; Kadiuska Rodríguez Arias; Ana Leonor González Sánchez (Información, Cultura y Sociedad, 2022)
The behavior in the search for information on the internet assumed by students of the Information Sciences career at the University of Holguín is analyzed. The research has a quantitative approach, not experimental, applied with a descriptive scope. A survey of nine questions was applied to a sample of 84 students, selected by random non-probabilistic sampling, namely: Type of study and year; ways in which information on the internet is searched and recovered; objectives that it pursues; consulted sources; formats and languages; search engines, platforms, social and academic networks used. It was observed that 60.7% always search alone and 90% never seek the help of a librarian. 67.8% always search academic google, while 60.7% point to Facebook as the social network they always go to and, to a lesser extent, to WhatsApp. Only 42.8% use academic social networks and in the last three years of the degree. Emphasis is placed on the need to offer better teaching orientation, so that students acquire information literacy that allows them to take advantage of academic social networks, as well as adapt study programs and include optional subjects from the first years, which contribute to develop the required skills. = Se analiza el comportamiento en la búsqueda de información en internet que asumen estudiantes de la carrera Ciencias de la Información en la Universidad de Holguín. La investigación tiene un enfoque cuantitativo, no experimental, aplicada con alcance descriptivo. Se aplicó una encuesta de nueve preguntas, a una muestra de 84 estudiantes, seleccionados por muestreo no probabilístico aleatorio, para conocer: modalidad de estudio y año; formas mediante las cuales busca y recupera información en internet; objetivos que persigue; fuentes que consulta; formatos e idiomas, buscadores, plataformas, redes sociales y académicas que utiliza. Se observó que el 60,7% siempre buscan solos y el 90% nunca se auxilian de un bibliotecario. El 67,8% siempre buscan en Google Académico, mientras que el 60,7% señalan a Facebook como red social a la que acuden siempre, y en menor medida a WhatsApp. Solo un 42,8% usan las redes sociales académicas y en los tres últimos años de la carrera. Se enfatiza en la necesidad de ofrecer una mejor orientación docente, para que los estudiantes adquieran la ALFIN que les permita aprovechar las ventajas de las redes sociales académicas, así como adecuar los programas de estudio e incluir asignaturas optativas desde los primeros años, que contribuyan a formar las habilidades requeridas.